ANALISIS PERTUMBUHAN EKONOMI INDONESIA TAHUN 1994-2020 - Affandi, A; Okta Rabiana Risma (universitas teuku umar, 2021)
This study aims to find out the factors that affect Indonesia's economic growth. To achieve the objectives of the study, this study used independent variables in the form of foreign investment (FDI), exchange rates, and interest rates. The data used in this research is secondary data from 1994-2020 sourced from various reports and compilations, especially publications from the Central Statistics Agency (BPS) and Bank Indonesia. The model used in this study was multiple linear regression with the method of analysis of the smallest square approach (Ordinary Least Square). The calculation results show that foreign investment variables, and exchange rates have a positive and significant effect on economic growth, while interest rates have a negative and significant effect on economic growth. The coefficient of determination (Adj.R2= 0.806) indicates that Indonesia's economic growth of 80.6 percent is influenced by foreign investment (FDI), exchange rates, and interest rates, while the remaining 19.4 percent is influenced by other factors outside this research. To increase the rate of economic growth, the government needs to increase the amount of FDI in Indonesia and maintain the stability of the rupiah exchange rate against the US dollar, thereinafter lowering the interest rate in order to increase domestic investment, in order to create an optimal national total production. Keywords : Economic Growth, Foreign Investment (PMA), Exchange Rate, and Interest Rate